PERSEPSI GURU SEKOLAH MENENGAH KEJURUAN TERHADAP PENDEKATAN STEM (SCIENCE, TECHNOLOGY, ENGGINEERING, AND MATHEMATIC) - tomi winata, - (2020)
Perception is a process of the use of knowledge that a person has in interpreting an object. This research aims to find out the perception of vocational high school teachers towards the approach of Science, Technolgy, Engineering, and Mathematics (STEM). Data retrieval is done online using instruments in the form of closed questionnaires. The population of this study is as many as vocational high school teachers from various regions as many as 22 people. It can be concluded that the perception of vocational high school teachers in Sumedang and Bandung, shows that teachers have a supportive view of the STEM approach, while other findings are that with supportive views on STEM teachers can apply the STEM approach, to the maximum but not supported by other components.